IMPLEMENTASI METODE EXTREME PROGRAMMING DALAM PENGEMBANGAN SISTEM INFORMASI PENGGAJIAN DI KAMPUS POLITEKNIK GANESHA GURU - Putra, Putu Maha (Universitas Lampung, 2025)
The payroll system implemented at Politeknik Ganesha Guru is still carried out manually, which often leads to data redundancy and inefficiencies in salary calculations. Therefore, a payroll information system is needed to improve efficiency and accuracy in calculating salaries for employees and lecturers. This study applies the Extreme Programming (XP) method as an approach in system development. XP is a software development method that focuses on short iterations, intensive communication between developers and users, and continuous feedback [1]. This payroll information system includes features for managing employee data, payroll data, and salary reports. Testing was conducted using the black-box testing method, which showed that the system functions according to user requirements. The results of this study indicate that the XP method can enhance efficiency and accuracy in the payroll process at Politeknik Ganesha Guru.